The impact of the global financial crisis on the efficiency and performance of Latin American stock markets; El impacto de la crisis financiera en la eficiencia y desempe\~no de mercados latinoamericanos de acciones - Zhenzhen Zhu; Zhidong Bai; Jo\~ao Paulo Vieito; Wing Keung Wong (Estudios de Economía, 2019)
We analyze the impact of the most recent global financial crisis (GFC) on the seven most important Latin American stock markets. Our mean-variance analysis shows that the markets are significantly less volatile and, in general, investors prefer to invest in the post-GFC period. Our results from the Hurst exponent and runs and variance-ratio tests show that the randomness and efficiency have been improved after the GFC. The stochastic dominance test shows that the markets are efficient, there is no arbitrage opportunity due to the GFC in our studying period, and, in general, investors prefer investing in the post-GFC period. The results confirm that the 2008 global financial crisis does have some positive impacts on Latin American stock markets. Our findings provide important information for investors and market regulators in their decision making in investment and setting regulations.
Keywords: G14; G15; 330; Latin American stock markets; randomness; market efficiency; stochastic dominance